Hierarchical Aluminum Vanadate Microspheres with Structural Water: High‐Performance Cathode Materials for Aqueous Rechargeable Zinc Batteries. Issue 9 (26th August 2020) - Pang, Qiang; He, Wei; Zhao, Hainan; Yu, Xiangyu; Wei, Yingjin; Tian, Ying; Xing, Mingming; Fu, Yao; Luo, Xixian
Abstract: Controlling morphology, adopting metal cations and introducing crystal water are three effective strategies to improve the electrochemical performance of various battery electrodes. However, the effects of simultaneously applying these three strategies to aqueous rechargeable zinc batteries (ARZBs) are rarely demonstrated. Herein, hierarchical H11 Al2 V6 O23.2 (HAVO) microspheres were successfully prepared using a simple hydrothermal method, and used as cathode material for ARZBs. The as‐prepared HAVO microspheres exhibited superior electrochemical performance than the dehydrated AlV3 O9 (AVO) microspheres, i. e. they have a larger specific capacity of 390.4 mA h g −1 at 100 mA g −1, a better rate capability of 191.4 mA h g −1 at 5000 mA g −1 and a higher cycling stability of up to 1000 cycles with a capacity retention of 80.9 %. The excellent electrochemical performance of HAVO is due to the synergistic effects of the shortened ion diffusion distance in primary HAVO nanosheets, the improved electronic conductivity, and structural stability by adopting Al 3+ into the lattice, the enhanced charge transfer properties and ion diffusion coefficient of the electrode due to the existence of crystal water. Therefore, this work may offer a new route for the design and synthesis of more advanced electrode materials for ARZBs. Abstract : Tailored struture for better performance : Hierarchical H11 Al2 V6 O23.2 (HAVO) microspheres were self‐assembled by a simple hydrothermal method and used as cathode materials for aqueous rechargeable zinc batteries. Compared to the dehydrated AlV3 O9 (AVO) sample, the HAVO microspheres possessed superior electrochemical kinetics, resulting in a larger reversible capacity, better cyclic stability and a more excellent rate capability.